Optimalisasi Handover Jaringan 4G Telkomsel di Kota Palembang - Muhamad Ilham Afwan; Nasron Nasron; Suroso Suroso (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2019)
Handovers on 4G networks such as Hard Handover when downlink and uplink must run well, if not then ongoing downlinks and uplinks will be hampered and even fail. This is closely related to potential customer satisfaction, thus the possibility of a handover failure resulting in dissatisfaction with operator users. Along with the high customer interest in 4G-LTE technology, this makes Telkomsel cellular operators maintain Quality & Performance where there is a decline in the quality of RSRP & SINR. One effort is to measure data in the field. The method in measuring data in the field is a Test Drive. Test Drive is a measurement method in a mobile communication system that aims to collect data on the measurement of signal quality of a network from the real direction in the field, so that it can know how the performance of the network.